Efektivitas Pendidikan Kewarganegaraan Dalam Etika Komunikasi Mahasiswa Ilmu Kelautan Angkatan 2022 - Riauroikha, Hilmalia Sesy; Tammardhiah, Rodhia; Juniati, Rita; Nahusona, Erick Suprianto; Putri, Gebby Cantika; Agustini, Raja Kharin; Sari, Nila Permata; Uly, Nadila; Rezky, Nathanael Pratama; Nafsiah, Kamila (Peneliti.net, 2024)
Civic education is a means of forming the character of citizens in accordance with the soul of the Indonesian nation. One of the characters that is formed is politeness that will be reflected in many things, one of which is communication. This study aims to determine effectiveness of the role of Civic Education in communication among students in the Marine Science Department at Universitas Maritim Raja Ali Haji. This research uses descriptive qualitative method. The data collection process uses literature study, observation, interviews, and offline questionnaire filling methods. The research population is 53 active Marine Science students from the 2022 class and the sample consists of 50 students. The results of this study show that the role of Civic Education in shaping polite communication character is not effective. This study shows normalization of using rude language when talking with peers because the politeness value that should be the foundation for communication is not implemented by these student.